Intervening in the Colonial Past: Review of Patrícia Lino’s The Survival Handbook of the Portuguese Discoverers in the Anti-Colonial World - Calça, Elaine (Satura, 2024)
Postcolonial studies was first coined as a term for academic purposes in the 1960s. In their early years, postcolonial studies primarily focused on critical engagement with literature and revealing the impact of colonization in everyday life. The Survival Handbook of the Portuguese Discoverers in the Anti-Colonial World belongs to this kind of literature. The book was published in Brazil (Edições Macondo) in October 2020, and it was later published in Portugal (Douda Correria) in December of that same year. The Survival Handbook, which has not yet been translated into English or German, makes a relevant critique that postcolonial studies need to investigate. In this article, I present the book’s postcolonial critique.